2016
DOI: 10.1177/1063426615618624
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Intensive Intervention Needs in Secondary Schools

Abstract: In this article, we provided descriptive and methodological illustrations of how to conduct systematic behavior screenings at the middle and high school levels to detect students with intensive intervention needs using one systematic screening tool: the Student Risk Screening Scale. We discussed the importance of systematic screening and presented data from secondary schools conducting systematic screenings to illustrate the proportion of students with these intensive needs. Results suggested 5.49% of the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Two critical but somewhat elusive issues for special education involve the identification of students’ intervention needs early in the developmental process and clarification of what works for whom (Conroy, 2016; Ludlow, 2014; Maggin et al, 2016). Considerable progress has been made with regard to the development of screening instruments to identify middle school students who experience adjustment difficulties in the academic, behavioral, and social domains (Lane et al, 2016, 2018). Although these approaches center on a variable-oriented framework, they could easily be adapted to include or be complemented by a person-oriented approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two critical but somewhat elusive issues for special education involve the identification of students’ intervention needs early in the developmental process and clarification of what works for whom (Conroy, 2016; Ludlow, 2014; Maggin et al, 2016). Considerable progress has been made with regard to the development of screening instruments to identify middle school students who experience adjustment difficulties in the academic, behavioral, and social domains (Lane et al, 2016, 2018). Although these approaches center on a variable-oriented framework, they could easily be adapted to include or be complemented by a person-oriented approach.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, middle school students with disabilities report elevated levels of social stress, a lack of support from peers, and a greater likelihood of social isolation and involvement in bullying both as a victim and as a perpetrator (Chen, Hamm, Farmer, Lambert, & Mehtaji, 2015; Evans & Eder, 1993; Rose & Gage, 2017). Similarly, middle school students with disabilities experience a range of behavior problems (Lane, Oakes, Lusk, Cantwell, & Schatschneider, 2016; Sullivan et al, 2015) and have elevated and increasing rates of chronic truancy compared with students without disabilities (Chen, Culhane, Metraux, Park, & Venable, 2016). These patterns suggest a need to further research subtypes of middle school students with disabilities who experience a variety of academic, social, and behavioral challenges.…”
Section: School Adjustment Of Middle School Students With Disabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings showed that the level of high risk for middle school students was 6.83%. A total of 17.40% of students were classified as moderate risk and 75.77% low risk (Lane, Oakes, Lusk, Cantwell, & Schatschneider, 2016).…”
Section: Importance Of Early and Accurate Identificationmentioning
confidence: 99%